2016
DOI: 10.1016/j.jneuroim.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

MSRV envelope protein is a potent, endogenous and pathogenic agonist of human toll-like receptor 4: Relevance of GNbAC1 in multiple sclerosis treatment

Abstract: Multiple sclerosis associated retrovirus envelope protein (MSRV-Env) was repeatedly detected in brain lesions and blood of multiple sclerosis (MS) patients. We performed the first pharmacological characterisation of MSRV-Env on recombinant and native human TLR4. MSRV-Env is a full and highly potent TLR4 agonist of endogenous origin. MSRV-Env induces TLR4-dependent pro-inflammatory stimulation of immune cells in vitro and in vivo, and impairs oligodendrocytes precursor cells differentiation to myelinating oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 54 publications
1
63
0
2
Order By: Relevance
“…HERV-W-Env was shown to promote monocyte maturation, DC differentiation, and release of proinflammatory cytokines, such as TNFα, IL1β, IL12β, and IL6 (34)(35)(36). In this respect, we have shown that HERV-W-Env affects the innate immune system of T1D patients, as the presence of this protein correlates with CD68 + cell detection in the exocrine pancreas ( Figure 3C).…”
Section: Indirect Immune-mediated Effects Of Herv-w-envmentioning
confidence: 75%
See 2 more Smart Citations
“…HERV-W-Env was shown to promote monocyte maturation, DC differentiation, and release of proinflammatory cytokines, such as TNFα, IL1β, IL12β, and IL6 (34)(35)(36). In this respect, we have shown that HERV-W-Env affects the innate immune system of T1D patients, as the presence of this protein correlates with CD68 + cell detection in the exocrine pancreas ( Figure 3C).…”
Section: Indirect Immune-mediated Effects Of Herv-w-envmentioning
confidence: 75%
“…This inhibition reached 50% at 100 ng/ml of HERV-W-Env in human β cells, without affecting cell viability ( Figure 5D). The underlying mechanism of this inhibition requires further investigations, though it has already been described that HERV-W-Env exerts its pathogenic effects through an interaction with the TLR4 receptor (35,36). From a T1D perspective, this mechanism appears relevant, as TLR4 is expressed by β cells (42)(43)(44).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Беручи до уваги, що на даний момент ендогенні ре-тровіруси досліджуються як етіологічний, а також пато-генетичний фактор РС, розроблено експериментальні засоби хворобо-модифікуючої терапії (ХМТ), мішенню яких є певні компоненти цих вірусів [17,18]. У даний час продовжуються два міжнародні рандомізовані клі-нічні дослідження з оцінки ефективності застосування моноклональних антитіл проти РСАРВ у хворих на РС [17,19].…”
Section: вступunclassified
“…У даний час продовжуються два міжнародні рандомізовані клі-нічні дослідження з оцінки ефективності застосування моноклональних антитіл проти РСАРВ у хворих на РС [17,19].…”
Section: вступunclassified